Selection, recombination, and G----A hypermutation of human immunodeficiency virus type 1 genomes. - Vartanian, J P (1991)
Human immunodeficiency virus type 1 (HIV-1) isolates are genetically so heterogeneous that they must be described in terms of populations of related but distinct genomes called quasispecies. A recent study of the influence of ex vivo culturing on HIV-1 quasispecies demonstrated that usually low-abundance genomes outgrew the more prominent forms. Here it is shown that multiple passages of an HIV-1 isolate on peripheral blood mononuclear cells resulted in the outgrowth of very minor forms. A single passage of equal proportions of supernatants to either of the established lymphocyte and monocyte cell lines Molt-3 and U937-2, respectively, resulted in the isolation of different sets of minor forms. Recombination between component sequences was observed. Extensive and monotonous base substitutions of G----A (G----A hypermutation) were evident in many sequences. A strong preference for the transition within the GpA dinucleotide was observed. Dislocation mutagenesis, in this case, a -1 slippage or dislocation of the primer with respect to the template, during DNA synthesis by the HIV-1 reverse transcriptase would explain this bias. When the consequences of polymerase errors, recombination, hypermutation, and instability are added to the genetic description of HIV-1, the real complexity of this virus starts to become apparent.